Perancangan Ui/Ux Aplikasi B-Side: Marketplace Fashion Minor Defect Untuk Mendukung SDGS 12 - Savira Narita Rachman; Mochamad Rafi Djaenal Pratama; Muhammad Ikhlasul Amal Akbar; Arista Pratama (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study designs the user interface and user experience (UI/UX) of the "B-Side" application, a dedicated e-marketplace for minor defect clothing. This innovation integrates the circular economy to support the 12th Sustainable Development Goal (SDGs) on responsible consumption and production. The design utilizes the Design Thinking method with five stages: empathize, define, ideate, prototype, and test. Since consumer reluctance to purchase minor defect clothing stems from doubts about the items' visual condition, the interface prioritizes transparency features, such as the Defect Highlight System, Defect Grading System, and product hygiene assurance. Usability testing was conducted online via the Maze platform, followed by satisfaction measurement using the System Usability Scale (SUS) questionnaire. Evaluation results show the B-Side prototype achieved an average SUS score of 86.25, placing it in the "Excellent" category, Grade A, and "Acceptable" status. In conclusion, B-Side's UI/UX design is highly intuitive, successfully mitigates consumer perceived risk, and effectively builds digital transactional trust to support sustainable fashion.